Pathological diagnosis experience and literature review of four cases suspected Lynch-like syndrome - Cheng, Bo; Liu, Shan; Ding, Shanshan; Quan, Lanju; Liu, Jinhong; Xu, Lin; Zhao, Huan; Guo, Jing; Sun, Suozhu (Frontiers in Oncology, 2025)
BackgroundAmong CRC patients with mismatch repair protein deficiency or microsatellite instability (MSI), up to 50% of cases lack germline mutations in MMR genes, BRAF mutations, or MLH1 promoter methylation. Such cases are defined as Lynch-like syndrome (LLS). LLS is a heterogeneous group of diseases that may include all the patients with cancers of the Lynch syndrome spectrum with MSI in which we don’t find a pathogenic variant in MMR genes. Although various methods have been proposed to distinguish Lynch and Lynch-like Syndrome, there is still a lack of consensus on the precise classification of these patients.MethodsFour cases of suspected Lynch-like syndrome encountered in daily clinical pathological diagnostic work were reported. The histopathological characteristics and molecular pathological changes of related tumors were analyzed, and the diagnosis and treatment progress of this disease were reviewed via literature.ResultsCombined with clinical findings and molecular pathological tests, 2 cases were diagnosed as Lynch-like syndrome (LLS), and 2 case was diagnosed as Lynch syndrome with atypical phenotype. Lynch-like syndrome-related tumors can occur in the colorectum and extraintestinal organs. Colorectal tumors show no specific locational or histological features, while extraintestinal tumors often exhibit poor differentiation and abundant interstitial lymphocyte infiltration. Patients with Lynch-like syndrome all exhibit tumoral lesions with loss of MMR protein (MLH1, PMS2, MSH2, MSH6) expression, microsatellite instability (MSI-L/MSI-H), wild-type BRAF, and negative MLH1 promoter methylation. However, heterogeneity exists in MMR protein expression, MSI status, and MLH1 promoter methylation among tumors at different sites in the same patient. No germline pathogenic mutations in MMR genes were detected in any Lynch-like syndrome, but one cases showed variant of uncertain significance in MMR, and two case (Lynch syndrome with atypical phenotype) had likely pathogenic mutation in MLH1.ConclusionExtraintestinal tumors associated with Lynch-like syndrome mostly exhibit histopathological characteristics and MMR/MSI changes similar to classic Lynch syndrome, but without pathogenic germline MMR mutations or MLH1 promoter methylation. Some suspected Lynch-like syndromes with likely germline pathogenic MMR mutations may represent Lynch syndrome with atypical phenotype. Most cases lack germline MMR mutations in normal tissues but harbor somatic MMR mutations in tumor tissues. Germline or somatic mutations in other genes related to MMR function may be observed in some cases.